'Poedicvlorvm oppida' : spazi urbani della Puglia Centrale in età Romana - Fioriello, Custode Silvio (Archaeopress Roman archaeology, 2017)
The indigenous persistence, texture, articulation, shape and functionality of the urban definition of the municipia in central Apulia demonstrate the nature of the complex history and settlement of this area in the long period between the age of Romanization and the 3rd century AD. The comprehensive collection and examination of the material evidence make it possible to reconstruct - for the first time, in an organic manner and in a global framework - the profile of the urban space of 'poediculorum oppida'.